Pregnanediols and breast milk jaundice. Issue 6 (June 1981) - Murphy, J F; Hughes, I; Verrier Jones, E R; Gaskell, S; Pike, A W
Abstract : Samples of breast milk collected from mothers of infants with breast milk jaundice were analysed for 5 beta-pregnane-3 alpha, 20 beta-diol, and other pregnanediols using gas chromatography-high resolution mass spectrometry. None was detected in any of the specimens and therefore it is unlikely to be the inhibitory factor in bilirubin conjugation. The plasma osmolalities of the infants, which were determined at the onset of jaundice, were within normal limits.